Population and Quality of Life - Ebigbola, J. A. (Obafemi Awolowo University Press, 2013)
Drawing on the experience of the developed countries, many developing countries embarked on, various development programmes in the post war era in order to improve the quality of life of their people. With the passing of the 1945 Colonial Development and Welfare Act, the British territories started to draw up long-term development plans. Similarly the Monnet plan prepared in France in 1946 was ...Later extended to the French overseas territories. About the same time. Long term economic. programmes were prepared for the Portuguese territories. •under the immediate impetus of the requirements of the United States • Marshall Plan aid. In an attempt to 'ca1Gh up' with the developed countries, the developing countries came to the conclusion that their development programmes would have to be implemented at a faster rate. Hence, there had been series of development plans aimed ,t •achieving the objective of improving the standard of living of the. masses in these societies